Involvement of Astrocytes and microRNA Dysregulation in Neurodegenerative Diseases: From Pathogenesis to Therapeutic Potential - Bai, Yang; Su, Xing; Piao, Lianhua; Jin, Zheng; Jin, Rihua (Frontiers in Molecular Neuroscience, 2021)
Astrocytes are the most widely distributed and abundant glial cells in the central nervous system (CNS). Neurodegenerative diseases (NDDs) are a class of diseases with a slow onset, progressive progression, and poor prognosis. Common clinical NDDs include Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD). Although these diseases have different etiologies, they are all associated with neuronal loss and pathological dysfunction. Accumulating evidence indicates that neurotransmitters, neurotrophic factors, and toxic metabolites that are produced and released by activated astrocytes affect and regulate the function of neurons at the receptor, ion channel, antigen transfer, and gene transcription levels in the pathogenesis of NDDs. MicroRNAs (miRNAs) are a group of small non-coding RNAs that play a wide range of biological roles by regulating the transcription and post-transcriptional translation of target mRNAs to induce target gene expression and silencing. Recent studies have shown that miRNAs participate in the pathogenesis of NDDs by regulating astrocyte function through different mechanisms and may be potential targets for the treatment of NDDs. Here, we review studies of the role of astrocytes in the pathogenesis of NDDs and discuss possible mechanisms of miRNAs in the regulation of astrocyte function, suggesting that miRNAs may be targeted as a novel approach for the treatment of NDDs.